PENGARUH PERBANDINGAN SARI TAPE JAGUNG DENGAN SARI JAHE DAN PERSENTASE GULA TERHADAP MUTU MINUMAN SARI TAPE JAGUNG-JAHE (The Effect of Ratio of Fermented Corn Liquid Fraction with Ginger Extract and Sugar Percentage on The Quality of Ginger and Corn Ferm - Indri Suci Astuti; Herla Rusmarilin; Hotnida Sinaga (Jurnal Rekayasa Pangan dan Pertanian, 2017)
ABSTRACT Extract of ginger and fermented corn drink is a drink from liquid fraction of fermented corn. Fermented corn liquid has a slightly sour taste, the addition of ginger and sugar could improve its organoleptic quality. The research was performed to find the effect of ratio of fermented corn liquid fraction with ginger extract and sugar percentage on the quality of ginger and fermented corn extract drink. This research designed was factorial randomized block design with two factors i.e. ratio of fermented corn liquid fraction with ginger extract (J) (55%:45% ; 60%:40% ; 65%:35% ; 70%:30%) and percentage of sugar (G) (5%; 10%; 15%; 20%). The parameters that analyzed were ph value, total soluble solid, total acid, total sugar, total  microbe, alcohol content, hedonic test and score test of color, flavor, taste. The best extract of ginger and fermented corn drink (J3G3) was at the ratio of fermented corn liquid fraction with ginger extract (65%:35%) and 15% sugar percentage. Keywords: Fermented Corn Liquid, Ginger Extract, Total Soluble Solid, Total Sugar ABSTRAK Minuman sari tape jagung-jahe merupakan minuman yang berasal dari sari tape jagung hasil fermentasi. Sari tape jagung memiliki rasa yang sedikit asam, sehingga dilakukan penambahan jahe dan gula untuk meningkatkan kualitas organoleptik minuman. Penelitian ini dilakukan untuk mengetahui pengaruh perbandingan sari tape jagung dengan sari jahe dan persentase gula terhadap mutu minuman sari tape jagung-jahe. Penelitian ini menggunakan rancangan acak kelompok faktorial dua faktor yaitu perbandingan sari tape jagung dengan sari jahe (J) (55%:45% ; 60%:40% ; 65%:35% ; 70%:30%) dan persentase gula (G) (5%; 10%; 15%; dan 20%). Parameter yang dianalisis adalah nilai ph, total padatan terlarut, total asam, total gula, total  mikroba, kadar alkohol, nilai hedonik (warna, aroma, rasa), dan nilai skor (warna, aroma, rasa). Minuman sari tape jagung-jahe terbaik terdapat pada perlakuan J3G3 yaitu perbandingan sari tape jagung dengan sari jahe (65%:35%) dan persentase gula 15%.   Kata Kunci: Sari Jahe, Sari Tape Jagung, Total Gula, Total Padatan Terlarut